«На земле еще много хороших вещей»: Рец. на кн.: «Человек эпохи: Ирина Белобровцева» [“Na zemle eshcho mnogo khoroshikh veshchei”: Review of _Chelovek epokhi: Irina Belobrovtseva_ by Aurika Meimre (ed.)] - Utgof, Grigori (Slavica Revalensia, 2021)
This is a review of a recently published book Chelovek epokhi: Irina Belobrovtseva (2021). The book consists of three parts: the first and longest is Irina Belobrovtseva’s autobiography followed by a publication of the correspondence between the Belobrovtsev family, Yuri Lotman and Zara Mints (from 1967 to 1986), and finally by Prof. Belobrovtseva’s list of publications.